(untitled) (Clinics, 2012)
OBJECTIVE: To analyze and compare the vertical component of ground reaction forces and isokinetic muscle parameters for plantar flexion and dorsiflexion of the ankle between long-distance runners, triathletes, and nonathletes. METHODS: Seventy-five males with a mean age of 30.26 (±6.5) years were divided into three groups: a triathlete group (n=26), a long-distance runner group (n = 23), and a non-athlete control group. The kinetic parameters were measured during running using a force platform, and the isokinetic parameters were measured using an isokinetic dynamometer. RESULTS: The non-athlete control group and the triathlete group exhibited smaller vertical forces, a greater ground contact time, and a greater application of force during maximum vertical acceleration than the long-distance runner group. The total work (180º/s) was greater in eccentric dorsiflexion and concentric plantar flexion for the non-athlete control group and the triathlete group than the long-distance runner group. The peak torque (60º/s) was greater in eccentric plantar flexion and concentric dorsiflexion for the control group than the athlete groups. CONCLUSIONS: The athlete groups exhibited less muscle strength and resistance than the control group, and the triathletes exhibited less impact and better endurance performance than the runners.